Pengaruh E-Trust Dan Perceived Value Terhadap Repurchase Intention Pada E-Commerce Shopee - Audrey Amadea; Christian Herdinata (BIP's JURNAL BISNIS PERSPEKTIF, 2022)
Electronic Commerce (e-commerce) is a transaction of buying and selling goods or services carried out between companies, households, individuals, governments and communities or other organizations that is carried out online. Consumer confidence in using e-commerce has increased from year to year. This can be seen from the increasing number of visits and transaction value. The increase in the number of visits and transactions that occurred during the pandemic led to an increase in consumer complaints in the e-commerce sector. The increasing number of transactions made online requires e-commerce companies to pay attention to several factors that can affect customer repurchase intention. Repurchase intention is an important factor for a company to be able to increase sales. In increasing customer repurchase intention, there are several influential variables, namely e-trust and perceived value variables. This study aims to determine the effect of e-trust and perceived value on repurchase intention in e-commerce Shopee. The population of this study are Shopee users. The sample in this study was taken using purposive sampling method as many as 120 respondents. The criteria used in this study include: (1) Shopee users aged 17 to 65 years; (2) Consumers who have made purchases at Shopee at least 10 times in the last 1 year, from April 2021 to March 2022. This study uses multiple linear regression analysis techniques. The results showed that e-trust had a significant effect on repurchase intention. These results indicate that the higher the e-trust perceived by the customer, the more often the customer will repurchas e intention on Shopee's e-commerce. The results of this study also show that perceived value has a significant effect on repurchase intention in Shopee e-commerce. This significant effect shows that if the customer feels and gets the benefits in accordance with expectations, the customer will repurchase intention.